Influenza A(H5N8) vaccine induces humoral and cell-mediated immunity against highly pathogenic avian influenza clade 2.3.4.4b A(H5N1) viruses in at-risk individuals - Liedes, Oona; Reinholm, Arttu; Ekström, Nina; Haveri, Anu; Solastie, Anna; Vara, Saimi; Rijnink, Willemijn F.; Bestebroer, Theo M.; Richard, Mathilde; de Vries, Rory D.; Jalkanen, Pinja; Lindh, Erika; et al. (Springer Science and Business Media LLC, 2026)
Finland faced an outbreak of highly pathogenic clade 2.3.4.4b A(H5N1) avian influenza in 2023, which spread from wild birds to fur farms. Vaccinations of at-risk individuals began in June 2024 using the MF59-adjuvanted inactivated A(H5N8) vaccine (Seqirus; A/Astrakhan/3212/2020, clade 2.3.4.4b). Here, in an observational study, we assessed vaccine-induced immune responses in occupational at-risk individuals participating in the phase IV trial, including virus-specific antibody (n = 39 individuals) and T-cell (n = 18 individuals) responses. Vaccination elicited functional antibodies against the vaccine virus and two heterologous clade 2.3.4.4b strains associated with outbreaks on Finnish fur farms and dairy cattle in the United States. Among previously unvaccinated individuals, seroprotection rates against the vaccine virus were 83% (95% CI 70–97%) by microneutralization assay (titre ≥20) and 97% (90–100%) by haemagglutination inhibition assay (titre ≥40). In those previously vaccinated against avian influenza, a single dose induced seroprotection. A(H5N8)-specific memory CD4+ T-cell responses were detectable, with ~5-fold increase in IFNγ secretion after two doses. These results demonstrate that the vaccine probably provides cross-protection against circulating H5 clade 2.3.4.4b viruses. EU Clinical Trial Number 2023-509178-44-00.